Nano-jet impingement cooling of a sinusoidal wavy hot surface by using an oriented L-shaped object under magnetic field with two phase mixture formulation - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Sci Ltd, 2023)
In this study, slot nano-jet impingement cooling of a wavy sinusoidal surface is analyzed by combined utilization of an oriented L-shaped object and magnetic field. A two phase mixture model of nanofluid is adopted. It is observed that the presence of the L-shaped object and its orientation are very influential on the local and average heat transfer performance. Magnetic field suppresses the vortices near the object and on the bottom all. The average Nusselt number (Nu) rises by 17.5% and 8.6% when its strength is varied for object orientations of te=-90 and te=90. When magnetic field inclination is concerned, the cooling performance improvements are in the range of 25.6%-53.9% depending upon the orientation of the object. The orientation of te=0 and te=45 are the most favorable cases in terms of thermal performance while significant variations in the average Nu are seen in the absence of magnetic field when varying the L-shaped object orientation. When compared to reference case of slot jet impingement (without magnetic field using pure fluid and without object), using nanofluid improves the cooling performance by about 8.4%. When object is installed at Ha=0, it rises by 27% at orientation of te=45. When magnetic field is used, additional rise of thermal performance with nanofluid is obtained up to 10% when compared to case by using only pure fluid.
Keywords: Jet impingement; Mixture model; Nanofluid; Magnetic field; Finite element method; L-shaped object